Selected neuroplastic effects of cognitive training in aging in MRI/fMRI studies - Emilia Leszkowicz (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
Several lines of research suggest that the loss of cognitive faculties in older people can be prevented and the risk of cognitive decline and dementia can be reduced. Cognitive training offers potential to modify cognitive abilities and their neural basis which can extend into advanced age. Examples of neuroplastic changes in the brain induced by multi-domain cognitive intervention and assessed by MRI/fMRI method in healthy aging and in people with cognitive impairment are presented. Cognitive training effects were observed both at behavioural and neural levels, which underlines the importance of interventions aimed at multiple lifestyle factors as possible strategies to support and improve cognitive status in advanced age. Effects of such interventions may result in considerable gains in terms of public health, especially in the face of aging societies.